2005
DOI: 10.1097/01.prs.0000161464.11134.c1
|View full text |Cite
|
Sign up to set email alerts
|

The Vascular Basis of Perforator Flaps Based on the Source Arteries of the Lateral Lumbar Region

Abstract: The authors have comprehensively described the anatomy of perforators of the lateral lumbar region of the trunk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 0 publications
1
32
1
1
Order By: Relevance
“…8 Although there have been a number of reports on the use of the LA perforator (LAP) flap for closure of lumbosacral defects and breast reconstruction, 8 there have been few anatomical studies to document the anatomy of the LA perforators. In 1999, Kato et al [9][10][11][12] were the first to describe the vascular territory of a single LA perforator, therefore validating the use of this vessel in harvesting LA island flaps and free flaps in this region. To date, there are at least 4 anatomical studies of the lumbar region.…”
mentioning
confidence: 98%
“…8 Although there have been a number of reports on the use of the LA perforator (LAP) flap for closure of lumbosacral defects and breast reconstruction, 8 there have been few anatomical studies to document the anatomy of the LA perforators. In 1999, Kato et al [9][10][11][12] were the first to describe the vascular territory of a single LA perforator, therefore validating the use of this vessel in harvesting LA island flaps and free flaps in this region. To date, there are at least 4 anatomical studies of the lumbar region.…”
mentioning
confidence: 98%
“…Usually there are 4 sets of arteries each giving off 4-8 perforators to supply a triangular territory of skin bordered medially by the midline, inferiorly by the region just below the iliac crest and laterally by a diagonal plane that extends from the inferomedial insertion of trapezius to the iliac crest. 10 In the present case ensuring that the lumbar artery perforators located adjacent to the erector spinae muscle were incorporated in the transposition flap, robust soft tissue coverage of the buttock region defect was achieved.…”
Section: Discussionmentioning
confidence: 91%
“…However, Offman et al 12 recently studied perforators of the superior epigastric artery and reported that this artery gives off a mean 5 Ϯ 1 perforators and supplies 150 Ϯ 40 cm 2 of abdominal integument. The superior epigastric artery can therefore be considered a desirable potential source of arteries for perforator flap transfer.…”
Section: Discussionmentioning
confidence: 96%